Dita.te —A Dictation Assessment Instrument with Automatic Analysis. - Saraiva, Daniela; Ramalho, Ana Margarida; Valente, Ana Rita; Rocha, Cláudia; Lousada, Marisa (Children, 2025)
Background/Objectives: To date, there are no validated tools that assess children's performance in connected text dictation tasks in European Portuguese using automated analysis. International studies were identified, but these primarily involved word dictation tasks and did not use automatic scoring tools. The present study aims to assess the reliability of the Dita.te (internal consistency and inter-rater reliability), a written assessment test based on a dictation task with automatic spreadsheet analysis, and establish normative data for text dictation tasks for children from 3rd to 6th grade. Methods: This study included 315 European Portuguese-speaking children from the 3rd to 6th grades. The Dita.te tool was used to assess orthographic errors based on phonological, morphological, and prosodic criteria. Descriptive statistics, percentiles, the inter-rater reliability and internal consistency were analyzed. Non-parametric tests compared performance by gender and school year due to a non-normal data distribution. Results: The Dita.te had excellent internal consistency (α = 0.929). The correlation between items scored highly (Intraclass Correlation Coefficient = 0.925). The number of errors decreased as the school year progressed, with errors affecting the syllable nucleus being the most frequent across all school years. These were followed by orthographic substitution errors, with grapheme omission being the most prevalent. Conclusions: Our findings suggest that orthographic competence is mostly stable before the 3rd grade, and the mismatches found in children with typical development show residual error in their orthographic performance.